PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, EFEKTIVITAS SISTEM PENGENDALIAN INTERN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN - Hartono Hartono; Ramdany Ramdany (STIE Muhammadiyah Jakarta, 2020)
This study aims to measure the effect of Government Accounting Standards (GAS), Effectiveness of Internal Control, Competence of Human Resources (HR) on the Quality of Financial Statements. Data sourced from questionnaires and processed using multiple regression analysis. The results showed that GAS, the effectiveness of the Government's Internal Control System, HR partially and simultaneously had a significant effect on the quality of financial statements.